2004
DOI: 10.1509/jmkg.68.4.90.42734
|View full text |Cite
|
Sign up to set email alerts
|

Return on Investment Implications for Pharmaceutical Promotional Expenditures: The Role of Marketing-Mix Interactions

Abstract: The authors empirically explore the revenue impact of marketing-mix variables and their interactions. The findings include the following: pharmaceutical direct-to-consumer advertising and detailing (sales force) affect demand synergistically, detailing raises price elasticity, and detailing has a higher return on investment than does direct-toconsumer advertising. The authors also discuss other implications and provide future research directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(203 citation statements)
references
References 42 publications
10
189
0
4
Order By: Relevance
“…This fi nding is consistent with analyses from the business literature on the impact of pharmaceutical detailing on prescribing behaviors (Ching and Ishihara, 2012;Fischer et al, 2009;Huddle, 2008;Katz et al, 2010;Mizik and Jacobson, 2004;Narayanan et al, 2004;Velasco et al, 2011). Although there are ethical considerations regarding the nexus of health care organizations and pharmaceutical companies (Huddle, 2008;Katz et al, 2010), important lessons might be learned from a more nuanced investigation of the detailing strategies that are being used in the context of SUD treatment.…”
Section: Discussionsupporting
confidence: 68%
“…This fi nding is consistent with analyses from the business literature on the impact of pharmaceutical detailing on prescribing behaviors (Ching and Ishihara, 2012;Fischer et al, 2009;Huddle, 2008;Katz et al, 2010;Mizik and Jacobson, 2004;Narayanan et al, 2004;Velasco et al, 2011). Although there are ethical considerations regarding the nexus of health care organizations and pharmaceutical companies (Huddle, 2008;Katz et al, 2010), important lessons might be learned from a more nuanced investigation of the detailing strategies that are being used in the context of SUD treatment.…”
Section: Discussionsupporting
confidence: 68%
“…When accounting has the upper hand over marketing, decisions are based on historical accounting records, with risk-taking discouraged, and marketing prescribed for achieving short-term goals. This is misguided practice, since marketing's long-term impact can be much stronger than its short-term impact (Pauwels, Silva-Risso, Srinivasan and Hanssens, 2004;Narayanan, Desiraju and Chintagunta, 2004).…”
Section: The Importance and Challenge Of Gaining Board Statusmentioning
confidence: 99%
“…It has been suggested that DTCA can help in expanding the market, in gaining market share, and in improving drug compliance by patients (Wosinska 2005). Empirical evidence suggests that DTCA has a significant impact on the category or product class sales (Wosinska 2003, Narayanan et al 2004, Iizuka and Jin 2005. At the same time, much of pharmaceutical advertising is at the brand level, and patients' requests for specific drug brands may influence physicians' prescribing Bala and Bhardwaj: Detailing vs. Direct-to-Consumer Advertising Management Science 56(1), pp.…”
Section: Introductionmentioning
confidence: 99%